A Numerical and Experimental Study of the Aerodynamics and Stability of a Horizontal Parachute. (18th August 2013) - Dawoodian, Mazyar; Dadvand, Abdolrahman; Hassanzadeh, Amir
Abstract : The flow past a parachute with and without a vent hole at the top is studied both experimentally and numerically. The effects of Reynolds number and vent ratio on the flow behaviour as well as on the drag coefficient are examined. The experiments were carried out under free-flow conditions. In the numerical simulations, the flow was considered as unsteady and turbulent and was modelled using the standardk -ε turbulence model. The experimental results reveal good agreement with the numerical ones. In both the experiments and numerical simulations, the Reynolds number was varied from 85539 to 357250 and the vent ratio was increased from zero to 20%. The results show that the drag coefficient decreases by increasing the Reynolds number for all the cases tested. In addition, it was found that at low and high Reynolds numbers, the parachutes, respectively, with 4% vent ratio and without vent are deemed more efficient. One important result of the present work is related to the effect of vent ratio on the stability of the parachute.